Exceptionally queer : Mormon peculiarity and U.S. nationalism - Mohrman, K. (University of Minnesota Press, 2022)
"K. Mohrman offers a powerful rethinking of Mormonism and its place in U.S. history, culture, and politics, arguing that Mormon peculiarity is a potent expression of U.S. exceptionalism. Exceptionally Queer ultimately shows how discussions of Mormonism in this country have been and continue to be central to ideas of what it means to be American"--